Targeted Disruption of TGF-β/Smad3 Signaling Modulates Skin Fibrosis in a Mouse Model of Scleroderma - Lakos, Gabriella (American Society for Investigative Pathology, 2004)
Transforming growth factor-β (TGF-β) is a potent stimulus of connective tissue accumulation, and is implicated in the pathogenesis of scleroderma and other fibrotic disorders. Smad3 functions as a key intracellular signal transducer for profibrotic TGF-β responses in normal skin fibroblasts. The potential role of Smad3 in the pathogenesis of scleroderma was investigated in Smad3-null (Smad3(−/−)) mice using a model of skin fibrosis induced by subcutaneous injections of bleomycin. At early time points, bleomycin-induced macrophage infiltration in the dermis and local TGF-β production were similar in Smad3(−/−) and wild-type mice. In contrast, at day 28, lesional skin from Smad3(−/−) mice showed attenuated fibrosis, lower synthesis and accumulation of collagen, and reduced collagen gene transcription in situ, compared to wild-type mice. Connective tissue growth factor and α-smooth muscle actin expression in lesional skin were also significantly attenuated. Electron microscopy revealed an absence of small diameter collagen fibrils in the dermis from bleomycin-treated Smad3(−/−) mice. Compared to fibroblasts derived from wild-type mice, Smad3(−/−) fibroblasts showed reduced in vitro proliferative and profibrotic responses elicited by TGF-β. Together, these results indicate that ablation of Smad3 is associated with markedly altered fibroblast regulation in vivo and in vitro, and confers partial protection from bleomycin-induced scleroderma in mice. Reduced fibrosis is due to deregulated fibroblast function, as the inflammatory response induced by bleomycin was similar in wild-type and Smad3(−/−) mice.